EVALUATING PERINATAL OUTCOMES IN HIGH-RISK PREGNANCIES USING THE MODIFIED COOPLAND’S SCORING SYSTEM AT A TERTIARY HOSPITAL - MARYAM , B; YASMEEN , H; ALAM , F; ALAM , S; MANAF , A; ASIF , M; SOHAIL , A; KHAN , M; HUSSAIN, Z; HUSSAIN, Z; et al. (Biological and Clinical Sciences Research Journal, 2024)
This study aims to thoroughly assess perinatal mortality rates, Apgar scores, birth weights, and neonatal complications within the first-week post-birth among high-risk pregnancies. Methods: During a prospective cohort study at Jinnah Postgraduate Medical Centre, Karachi, from October 2023 to May 2024, we evaluated outcomes in 664 high-risk pregnant women using systematic random sampling. Participants, with singleton pregnancies of 24 weeks or more gestation, were stratified by risk level. Data included demographic details, socioeconomic status, BMI, and pregnancy history. Maternal outcomes, such as mode of delivery and postpartum haemorrhage requiring transfusion, and perinatal outcomes, including birth weight and APGAR scores, were assessed. Statistical analysis emphasized odds ratios, with p < 0.05 considered significant. Ethical approval was obtained, and all participants provided informed consent. Results: This prospective cohort study at Jinnah Postgraduate Medical Centre from October 2023 to May 2024 involved 664 high-risk pregnant women categorized by standard risk scoring. Participants were predominantly low-risk (65.77%), followed by moderate-risk (19.88%) and high-risk (14.35%). Key findings included increased rates of cesarean sections, postpartum haemorrhage, premature births, low birth weight, adverse APGAR scores, NICU admissions, and perinatal mortality with escalating risk levels. Statistical analyses revealed significant associations and elevated odds ratios for adverse outcomes among higher-risk groups, underscoring the importance of risk assessment in managing maternal and perinatal health outcomes. Conclusion: Our study highlights the urgent importance of identifying and effectively managing high-risk pregnancies. We discovered that these pregnancies are associated with significantly elevated risks of complications such as Cesarean deliveries, postpartum haemorrhage, preterm births, low birth weights, low 5-minute APGAR scores, NICU admissions, and perinatal mortality. Implementing a straightforward, non-invasive risk-scoring system can facilitate early detection of high-risk cases, enabling timely and tailored interventions that can greatly improve outcomes for both mothers and infants.